Synthesis and binding behaviour of new isomers of bis-thiourea - Imran Fakhar,; Bohari Muhammad Yamin,; Sahilah Abdul Mutalib,; Siti Aishah Hasbullah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The two new symmetrical bis-thiourea compounds, 2,2’-[{(terephthaloylbis(azanediyl)bis (carbonothioyl)bis(azanediyl)}bis(4-methylpentanoicacid)] 1A and 2,2’-[{(isophthaloylbis (azanediyl)bis(carbonothioyl)bis(azanediyl)}bis(4-methylpentanoic acid)] 1B have been synthesized by reacting terephthaloyl/isophthaloyl chloride and L-leucine in high yields. Newly synthesized bis-thiourea derivatives were characterized using FTIR, 1D NMR, 2D NMR, MS spectrometry and Elemental analysis. Their binding properties with various cations were also carried out using UV-vis titration experiments. Both isomers exhibited effective binding against Ag+, Cu2+, Ni2+, Hg2+, Pb2+, Fe2+, and Fe3+ in the presence of other cations, such as Na+, Co2+, Cd2+, Zn2+, Mn2+, Mg2+, Ca2+, Sn2+, and Al3+. Stoichiometries of the host-guest complexation for both isomers were found to be 1:4 by plotting molar-ratio curves. Pearson Product moment correlation coefficient was in the range of 0.83-0.99 and nonlinear regression equation was used to calculate dissociation constant (Kd). Both compounds displayed weak antibacterial activities against gram-positive and gram negative bacteria. Cytotoxicity testing on CCD841 Normal human colon epithelial cell line showed that both compounds are non-toxic, with an IC50 value of 1.50 mg/mL.